Enhanced biogas production from municipal solid waste via digestion with cow manure: A case study - Mohamed Zainab B.; Fattah Mohammed Y.; Shehab Esraa Q.; Shamkhy Ali G. (Open Engineering)
Anaerobic digestion (AD) of feedstocks yields biogas, a potentially useful new energy source. This study looked into the anaerobic co-digestion of cow dung and organic garbage to produce biogas. An anaerobic biodigester, with a volume of 20 L, was used to digest organic waste (OW) and to trace the changes that occur during the AD process. It was equipped with tools that ensure complete control of the conditions affecting anaerobic biological reactions such as temperature, pH function, and mixing speed. Therefore, an anaerobic biodigester was designed to contain such biological transformations and to improve the biogas production process from OW. Based on the present investigation, the AD of OW was improved by integrating the substrate with sewage sludge or cow manure (CM) during the digestion process to provide the basic microorganisms to complete the digestion process. Feeding into the digester was a blend of 100 kg of cow dung (CM) and OW per day, diluted 1:1 with water. A gasbag was used to capture the methane that resulted. Biogas production began on the seventh day after the substrate was fed into the digester. A performance test was carried out on the produced biogas to determine its composition. For OW–CM, the generated biogas’s methane (CH4) concentration was determined to be 60%, but the rates of decline for TS and VS were 57 and 50.6%, respectively. Anaerobic biodegradation of OW–CM experiments was observed at 37°C, a mesophilic temperature. For OW–CM, the pH value was 6.7. After being adjusted to standard circumstances, the cumulative volume of methane produced which had been recorded as 4,914 mL became 3964.5 mL.